Ecological, Socioeconomic and Nutraceutical Values of Zizania latifolia (Kambong): A Wetland Grass for Sangai Deer & Human Population - Dimri, Rakhee; Das, Kadambini; Devi, Rajkumari Supriya; Kumar, Sanjeet; Kumar, Niraj; Das, Anuradha (Indian Forester, 2024)
Zizania latifolia (Griseb.) Hance ex F. Muell., is an important wetland flora of Loktak Lake, Manipur, that has ecological, economic and nutraceutical values. This grass species is not only important for its nutraceutical values but also important as it is also one of the most preferred foods of Sangai deer [Rucervus eldii eldii], an endangered and endemic mammal of Manipur. The present study highlights the importance of Z. latifolia, a wetland tall grass species locally known as Kambong with respect to its nutraceutical, food, economic, and ecological values. The survey of the flora of Loktak Lake, communication with some local inhabitants, visiting market places in Manipur, and literature survey were carried out to consolidate the information on Z. latifolia. The concise information is presented here, along with photographs of the studied plant, ecological significance, economic values, and traditional food systems, for better understanding and sustainable utilization.